Wear-resistant anticorrosive coating and preparation method thereof
By combining modified nanotitanium dioxide particles, MXenes and metal organic frames with resin materials, the problem that existing coatings are difficult to meet multiple performance requirements at the same time is solved, and the multifunctional integration and performance improvement of the coating is achieved, and it is suitable for a variety of optical electronic devices.
Patent Information
- Application Number
- CN202411844222.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing anti-corrosion and wear-resistant coatings have unreasonable aspects in the formulation, which is difficult to meet multiple performance requirements at the same time, resulting in limited application range and complex preparation process.
Modified nanotitanium dioxide particles, MXenes and metal organic frames are combined with materials such as silicone resin, polyurethane resin or fluoride polymer, and combined with functional additives to form a wear-resistant and anti-corrosion coating.
It significantly improves the wear resistance, impact resistance, conductivity and thermal management capabilities of the coating, realizes the integration of multiple functions, and is suitable for a variety of types of optical electronic devices, extending the service life of the device.
Smart Images

Figure CN119775889A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant and anti-corrosion coatings, and in particular to a wear-resistant and anti-corrosion coating and a preparation method thereof. Background Art
[0002] In the field of optical electronic devices, such as solar cells, photodetectors, light-emitting diodes and camera lenses, the performance of the coating directly affects the overall performance and service life of the device. Although the existing anti-corrosion and wear-resistant coatings have provided protection to a certain extent, there are some unreasonable aspects in their formulations, which lead to some deficiencies in the actual application of the coatings.
[0003] Traditional anti-corrosion and wear-resistant coatings will add some functional additives during the preparation to improve the performance. Usually, a combination of nano-titanium dioxide, organic resins and additives (ultraviolet absorbers, antistatic agents, etc.) is used. However, this single combination is difficult to meet the requirements of multiple performances at the same time. For example, although the existing coatings have anti-corrosion and wear resistance, they lack the integration of multiple functions (optical properties, adhesion stability, conductivity and thermal management, etc.), which makes the application range relatively low and cannot be widely used in multiple different types of devices. If multiple functional requirements are to be met at the same time, a combination of multiple materials is required. This method not only increases costs, but also makes the process relatively complicated during the preparation process. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant and anti-corrosion coating and a preparation method thereof to solve the problems raised in the above background technology.
[0005] To achieve the above object, on the one hand, the present invention provides a wear-resistant and anti-corrosion coating, comprising the following raw materials:
[0006] 5-7 parts by weight of modified nano titanium dioxide particles, obtained by modifying nano titanium dioxide with a reinforcing material;
[0007] 2-4 parts by weight of MXenes, a class of two-dimensional materials with unique properties, composed of transition metal carbides, nitrides or carbonitrides, prepared by selective etching of MAX phase (a ternary layered compound); MXenes have excellent electrical and thermal conductivity, which helps to improve the electrical conductivity and heat dissipation capacity of the coating. This is especially important for devices such as light-emitting diodes and photodetectors that require good thermal management; its high strength and toughness can significantly improve the wear resistance and impact resistance of the coating, and it exhibits good chemical stability in a variety of environments and can effectively resist corrosion and oxidation;
[0008] 2-4 parts by weight of a metal organic framework. The porous structure of the metal organic framework can provide additional adsorption and storage capacity for the coating, which helps to improve corrosion resistance and wear resistance. Secondly, the metal nodes in the metal organic framework can form chemical bonds or strong interactions with the reinforcing materials in the nano-titanium dioxide, thereby enhancing the stability and functionality of the composite material.
[0009] 85 parts by weight of resin material, one of silicone resin, polyurethane resin, epoxy resin or fluoride polymer is used; silicone resin, polyurethane resin and fluoride polymer all have good weather resistance and chemical resistance, and the combination with MXenes and MOFs further improves the anti-corrosion performance of the coating; polyurethane resin and epoxy resin provide excellent mechanical strength and toughness, and enhance the wear resistance and impact resistance of the coating; the high conductivity and thermal conductivity of MXenes combined with silicone resin or polyurethane resin improve the conductivity and heat dissipation capacity of the coating; the high transparency and controllable refractive index of silicone resin and fluoride polymer, combined with the light absorption characteristics of modified nano titanium dioxide particles, optimize the optical properties of the coating; by selecting different resin matrices, the integration of multiple functions such as anti-static, anti-fog, anti-fouling, etc. can be achieved, which provides possibilities for the development of multifunctional coatings in the future; silicone resin, polyurethane resin, epoxy resin and fluoride polymer as matrix materials or adhesives not only enhance the basic properties of the coating, but also achieve higher performance improvement through synergistic effects with modified nano titanium dioxide particles, MXenes and metal organic frameworks.
[0010] 3-5 parts by weight of additives, at least one of ultraviolet absorbers, antioxidant additives, light stabilizers, and antistatic agents. By adding these functional additives, the coating not only has basic anti-corrosion and wear resistance, but also obtains additional protection and functions, further improving its comprehensive performance in various applications, specifically:
[0011] The ultraviolet absorber is one of UV-9 and UV-531;
[0012] The antioxidant additive is one of antioxidant 1010 or antioxidant 168;
[0013] The light stabilizer is one of Tinuvin326 and Tinuvin234;
[0014] The antistatic agent is one of polyether modified polysiloxane or quaternary ammonium salt antistatic agents.
[0015] As a further improvement of the technical solution, the modified nano titanium dioxide particles are one of iron-doped nano titanium dioxide particles, nitrogen-doped nano titanium dioxide particles, carbon nanotube-enhanced nano titanium dioxide particles, and nano titanium dioxide particles coated with polyacrylate on the surface. By doping with elements such as iron or nitrogen, the modified nano titanium dioxide particles can expand their light response range, thereby improving the absorption efficiency of visible light, which is particularly important in solar cells and photodetectors; surface modification and coating treatment can improve the dispersibility and stability of nano titanium dioxide particles, reduce surface defects, and thus enhance the weather resistance and mechanical strength of the coating; by controlling the size and morphology of nano titanium dioxide particles, the refractive index of the coating can be optimized, the reflection loss can be reduced, and the light transmittance can be improved.
[0016] As a further improvement of the technical solution, the metal organic framework adopts one of iron-based metal organic framework materials, zinc-based metal organic framework materials, copper-based metal organic framework materials, and aluminum-based metal organic framework materials. The metal organic framework has a high specific surface area and an adjustable pore structure, which can adsorb and store moisture and harmful gases, and improve the anti-corrosion performance of the coating; by selecting different metal ions and organic ligands, the metal organic framework can give the coating specific functions, such as photocatalysis, gas adsorption, etc. The metal nodes in the metal organic framework form chemical bonds or strong interactions with the doped elements (such as iron and nitrogen) in nano-titanium dioxide, which enhances the stability and functionality of the material.
[0017] On the other hand, the present invention provides a method for preparing the wear-resistant and anti-corrosion coating described in any one of the above, comprising the following steps:
[0018] S1, reinforcing material modifies nano titanium dioxide to obtain modified nano titanium dioxide particles;
[0019] S2, preparation of MXenes by selective etching of MAX phase;
[0020] S3, preparation of metal organic frameworks by solvothermal method;
[0021] S4. Mixing the modified nano-titanium dioxide particles, MXenes and metal organic frameworks with resin materials and additives to form a coating material.
[0022] In the present invention, the combination of MXenes and metal organic frameworks provides excellent anti-corrosion performance. The high chemical stability of MXenes plus the porous structure of the metal organic framework can effectively prevent the erosion of moisture and harmful gases; the high strength and toughness of MXenes combined with the structural stability of the metal organic framework significantly improve the wear resistance and impact resistance of the coating; the high electrical conductivity and thermal conductivity of MXenes combined with the porous structure of the metal organic framework not only improve the electrical conductivity of the coating, but also enhance the heat dissipation capacity and extend the service life of the device. At the same time, the introduction of MXenes and metal organic frameworks enables the coating to remain stable in a variety of environments and is suitable for applications under various harsh conditions; by selecting different metal organic frameworks and MXenes, the integration of multiple functions can be achieved, such as photocatalysis, gas sensing, etc.
[0023] Secondly, the controllable synthesis method of metal-organic frameworks and the selective etching technology of MXenes allow the microstructure and properties of the coating to be better regulated, thereby achieving more precise design and optimization; the good dispersibility and compatibility of MXenes and metal-organic frameworks allow them to be easily mixed with nano-titanium dioxide particles and other materials, simplifying the preparation process and improving production efficiency.
[0024] The high transparency and controllable refractive index of modified nano-titanium dioxide particles, combined with the structural characteristics of MXenes and metal-organic frameworks, can further reduce reflection, improve transmittance, and optimize optical properties; the combination of the porous structure of the metal-organic framework and the photocatalytic properties of nano-titanium dioxide particles can realize the self-cleaning function of the coating and reduce maintenance costs.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] In the wear-resistant and corrosion-resistant coating and its preparation method, by introducing modified nano titanium dioxide particles, MXenes and metal organic frameworks, combined with silicone resin, polyurethane resin, epoxy resin or fluoride polymer, and functional additives, the irrationality of the existing anti-corrosion and wear-resistant coating in the formula is solved. Through the compounding of the raw materials of the present invention, the basic performance of the coating is improved, and the coating is given additional functions, with multiple functions integrated, the problem of the coating having only a single performance is solved, and a wider range of applications, higher levels of protection and performance improvement are provided for optical electronic devices. At the same time, the method adopted simplifies the preparation process and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an overall flow chart of Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1: The embodiment of the present invention provides a wear-resistant and anti-corrosion coating for solar cells, comprising the following raw materials:
[0030] Iron-doped nano-titanium dioxide particles, 5 parts by weight;
[0031] MXenes, 3 parts by weight;
[0032] Iron-based metal organic framework material (Fe-MIL-101), 2 parts by weight;
[0033] Silicone resin, 85 parts by weight;
[0034] Ultraviolet light absorber, 5 parts by weight, the ultraviolet light absorber is evenly dispersed in the silicone resin by physical mixing, absorbs ultraviolet light and converts it into heat energy, protecting the coating from ultraviolet damage.
[0035] Preparation method:
[0036] Through the sol-gel method, iron ions are introduced into the titanium dioxide lattice to form iron-doped nano-titanium dioxide particles. The presence of iron ions can change the electronic structure of titanium dioxide, expand its light response range, and improve its photocatalytic activity and optical properties. Specifically:
[0037] 0.5 parts by weight of titanium dioxide powder and 0.05 parts by weight of ferric sulfate nonahydrate were dissolved in 100 parts by weight of ethanol, stirred at 7° C. for 4 hours, then dried at 100° C. for 12 hours, and finally calcined at 500° C. for 2 hours to obtain iron-doped nano titanium dioxide particles;
[0038] MXenes are prepared by selectively etching the MAX phase (titanium aluminum carbide) and removing the Al layer using HF solution to obtain MXene sheets with high conductivity and mechanical strength. The surface is rich in hydroxyl and oxygen groups, with good hydrophilicity and conductivity. Specifically:
[0039] 2 parts by weight of titanium carbide aluminum powder was added to 40 parts by weight of 40% HF solution, stirred at 35°C for 24 hours, washed with deionized water until the pH value was 6-7, and then vacuum dried at 60°C for 12 hours to obtain the product;
[0040] The iron-based metal organic framework material is prepared by a solvothermal method, with ferric chloride hexahydrate as the metal source and trimesic acid as the organic ligand, and the iron-based metal organic framework material is generated by reaction under solvothermal conditions. Specifically:
[0041] 0.2 parts by weight of ferric chloride hexahydrate and 0.2 parts by weight of trimesic acid are dissolved in 10 parts by weight of N,N-dimethylformamide, and subjected to solvent thermal reaction at 100° C. for 24 hours, followed by cooling, filtering, washing and drying at 60° C. for 12 hours to obtain an iron-based metal organic framework material, wherein iron ions form coordination bonds with trimesic acid to construct a porous structure;
[0042] The iron-doped nano-titanium dioxide particles, MXenes and iron-based metal organic framework materials are uniformly dispersed in a silicone resin solution, a UV absorber is added, mixed evenly and coated on the surface of a solar cell, and then cured to obtain a wear-resistant and anti-corrosion coating for solar cells. Specifically:
[0043] 5 parts by weight of iron-doped nano-titanium dioxide particles, 3 parts by weight of MXenes and 2 parts by weight of iron-based metal organic framework materials are uniformly dispersed in 85 parts by weight of silicone resin solution, 5 parts by weight of ultraviolet absorber are added, mixed evenly, and the mixture is coated on the surface of the solar cell by spraying or dipping, and then cured at 120°C for 2 hours.
[0044] The introduction of iron ions in this embodiment increases the visible light response range of titanium dioxide and improves the light absorption efficiency; MXenes provide high conductivity and mechanical strength, and enhance the weather resistance and mechanical properties of the coating; the iron ions in the iron-based metal organic framework material can form chemical bonds or strong interactions with the iron ions in the iron-doped nano titanium dioxide particles, enhancing the stability of the material. The porous structure of the iron-based metal organic framework material can absorb and store moisture and harmful gases, improving the anti-corrosion performance; the silicone resin is used to provide good adhesion and weather resistance, ensuring the long-term stability of the coating; the ultraviolet absorber is used to reduce the damage of ultraviolet rays to the coating and extend the service life.
[0045] Embodiment 2: The embodiment of the present invention provides a wear-resistant and anti-corrosion coating for a photoelectric detector, comprising the following raw materials:
[0046] Nitrogen-doped nano-titanium dioxide particles, 6 parts by weight;
[0047] MXenes, 3 parts by weight;
[0048] Zinc-based metal organic framework material (ZIF-8), 3 parts by weight;
[0049] Polyurethane resin, 85 parts by weight;
[0050] Antioxidant additive, 3 parts by weight, the antioxidant additive is evenly dispersed in the polyurethane resin by physical mixing to capture free radicals and prevent oxidation reactions.
[0051] Preparation method:
[0052] Nitrogen-doped nano-titanium dioxide particles were prepared by hydrothermal method. The introduction of nitrogen element can expand the light response range of titanium dioxide and improve its absorption capacity of visible light. Specifically:
[0053] 0.5 parts by weight of titanium dioxide powder and 0.05 parts by weight of urea were dissolved in 100 parts by weight of ethanol, stirred at 70° C. for 4 hours, then dried at 100° C. for 12 hours, and finally calcined at 500° C. for 2 hours to obtain nitrogen-doped nano titanium dioxide particles;
[0054] MXenes were prepared by selectively etching the MAX phase, and the specific method was the same as in Example 1;
[0055] The zinc-based metal organic framework material is prepared by a solvothermal method, with zinc nitrate hexahydrate as a metal source and 2-methylimidazole as an organic ligand, and the zinc-based metal organic framework material is generated under solvothermal conditions. Specifically:
[0056] 0.2 parts by weight of zinc nitrate hexahydrate and 0.2 parts by weight of 2-methylimidazole are dissolved in 10 parts by weight of methanol, stirred at room temperature for 24 hours, and then filtered, washed and dried at 60° C. for 12 hours to prepare a zinc-based metal organic framework material, in which zinc ions form coordination bonds with 2-methylimidazole to construct a porous structure;
[0057] Nitrogen-doped nano-titanium dioxide particles, MXenes and zinc-based metal organic framework materials are mixed with polyurethane resin and antioxidant additives to form a uniform suspension, which is applied to the surface of the photodetector by spraying or dipping, and then baked and cured to obtain a wear-resistant and anti-corrosion coating for the photodetector. Specifically:
[0058] 6 parts by weight of nitrogen-doped nano-titanium dioxide particles, 3 parts by weight of MXenes and 3 parts by weight of zinc-based metal organic framework materials are uniformly dispersed in 85 parts by weight of polyurethane resin, 3 parts by weight of antioxidant additives are added, mixed evenly, and the mixture is applied to the surface of the photodetector by spraying or dipping, and then baked at 100°C for 2 hours.
[0059] The introduction of nitrogen in this embodiment expands the light response range of titanium dioxide and improves its absorption capacity for visible light; MXenes provide high conductivity and mechanical strength, and enhance the weather resistance and mechanical properties of the coating; the chemical bonds or strong interactions between zinc ions in the zinc-based metal organic framework material and nitrogen atoms in the nitrogen-doped nano-titanium dioxide particles enhance the stability of the composite material. The porous structure of the zinc-based metal organic framework material can absorb and store moisture and harmful gases, and improve the anti-corrosion performance; polyurethane resin is used to provide good mechanical strength and chemical resistance to ensure the long-term stability of the coating; antioxidant additives are used to prevent oxidation reactions and extend the service life of the coating.
[0060] Embodiment 3: The embodiment of the present invention provides a wear-resistant and anti-corrosion coating for light-emitting diodes, comprising the following raw materials:
[0061] Carbon nanotube-reinforced nano-titanium dioxide particles, 7 parts by weight;
[0062] MXenes, 4 parts by weight;
[0063] Copper-based metal organic framework material (HKUST-1), 2 parts by weight;
[0064] Epoxy resin, 85 parts by weight;
[0065] Light stabilizer, 3 parts by weight, the light stabilizer is evenly dispersed in the epoxy resin by physical mixing, absorbs high-energy ultraviolet rays and converts them into low-energy heat energy to prevent light degradation.
[0066] Preparation method:
[0067] Carbon nanotubes are synthesized by CVD method and compounded with nano-titanium dioxide particles to form carbon nanotube-enhanced nano-titanium dioxide particles to improve electrical conductivity and thermal conductivity. Specifically:
[0068] The carbon nanotubes were synthesized by CVD method and mixed with nano-titanium dioxide particles at a ratio of 1:10; the nano-titanium dioxide particles were ground in a ball mill for 24 hours to obtain carbon nanotube-reinforced nano-titanium dioxide particles;
[0069] MXenes were prepared by selectively etching the MAX phase, and the specific method was the same as in Example 1;
[0070] The copper-based metal organic framework material is prepared by a solvothermal method, using copper nitrate trihydrate as a metal source and trimesic acid as an organic ligand to react under solvothermal conditions to generate the copper-based metal organic framework material. Specifically:
[0071] 0.2 parts by weight of copper nitrate trihydrate and 0.2 parts by weight of trimesic acid are dissolved in 10 parts by weight of DMF, and subjected to solvent thermal reaction at 100° C. for 24 hours, followed by cooling, filtering, washing and drying at 60° C. for 12 hours to obtain a copper-based metal organic framework material, wherein copper ions form coordination bonds with trimesic acid to construct a porous structure;
[0072] The carbon nanotube-reinforced nano-titanium dioxide particles, MXenes and copper-based metal organic framework materials are mixed with epoxy resin and light stabilizer to form a uniform coating material, which is then covered on the LED chip by spin coating or spray coating, and then cured by ultraviolet light to obtain a wear-resistant and anti-corrosion coating for light-emitting diodes. Specifically:
[0073] 7 parts by weight of carbon nanotube-reinforced nano-titanium dioxide particles, 4 parts by weight of MXenes and 2 parts by weight of copper-based metal organic framework materials are uniformly dispersed in 85 parts by weight of epoxy resin, 3 parts by weight of light stabilizer are added, mixed evenly, and the mixture is covered on the LED chip by spin coating or spray coating, and then cured under ultraviolet light for 2 hours.
[0074] In this embodiment, the introduction of carbon nanotubes significantly improves the electrical conductivity and thermal conductivity of nano-titanium dioxide particles, and enhances the heat dissipation performance and stability of the LED; MXenes provide high electrical conductivity and mechanical strength, and enhance the weather resistance and mechanical properties of the coating; the chemical bonds or strong interactions between the copper ions in the copper-based metal organic framework material and the titanium dioxide and carbon nanotubes in the carbon nanotube-reinforced nano-titanium dioxide particles enhance the stability of the composite material; the porous structure of the copper-based metal organic framework material can adsorb and store moisture and harmful gases, and improve the anti-corrosion performance; epoxy resin is used to provide good mechanical strength and adhesion to ensure the long-term stability of the coating; the light stabilizer is used to prevent degradation caused by light and extend the service life of the coating.
[0075] Embodiment 4: The embodiment of the present invention provides a wear-resistant and anti-corrosion coating for a camera lens, comprising the following raw materials:
[0076] 5 parts by weight of nano titanium dioxide particles coated with polyacrylate;
[0077] MXenes, 2 parts by weight;
[0078] Aluminum-based metal organic framework material (MIL-53 (Al)), 4 parts by weight;
[0079] Fluoride polymer, 85 parts by weight;
[0080] Antistatic agent, 4 parts by weight, the antistatic agent is evenly dispersed in the fluoride polymer by physical mixing to increase surface conductivity and prevent static electricity accumulation.
[0081] Preparation method:
[0082] Nano-titanium dioxide particles were synthesized by a sol-gel method, and the surface was modified by using a silane coupling agent, and then further coated with polyacrylate to obtain nano-titanium dioxide particles coated with polyacrylate. Specifically:
[0083] 0.5 parts by weight of titanium dioxide powder and 0.05 parts by weight of γ-aminopropyltriethoxysilane are dissolved in 100 parts by weight of ethanol, stirred at 70° C. for 4 hours, and then dried at 100° C. for 12 hours. The treated titanium dioxide powder is mixed with 0.05 parts by weight of polyacrylate, and ground in a ball mill for 24 hours to obtain nano titanium dioxide particles with surface coated with polyacrylate;
[0084] MXenes were prepared by selectively etching the MAX phase, and the specific method was the same as in Example 1;
[0085] The aluminum-based metal organic framework material is prepared by a solvothermal method, with aluminum nitrate nonahydrate as the metal source and terephthalic acid as the organic ligand, and the aluminum-based metal organic framework material is generated by reaction under solvothermal conditions. Specifically:
[0086] 0.2 parts by weight of aluminum nitrate nonahydrate and 0.2 parts by weight of terephthalic acid are dissolved in 10 parts by weight of DMF, and subjected to solvent thermal reaction at 100° C. for 24 hours, followed by cooling, filtering, washing and drying at 60° C. for 12 hours to obtain an aluminum-based metal organic framework material, wherein aluminum ions form coordination bonds with terephthalic acid to construct a porous structure;
[0087] Nano-titanium dioxide particles coated with polyacrylate, MXenes and aluminum-based metal organic framework materials are mixed with fluoride polymers and antistatic agents to form a coating material, which is uniformly deposited on the surface of a camera lens by vacuum sputtering or evaporation technology to obtain a wear-resistant and anti-corrosion coating for a camera lens. Specifically:
[0088] 5 parts by weight of nano-titanium dioxide particles coated with polyacrylate, 2 parts by weight of MXenes and 4 parts by weight of aluminum-based metal organic framework materials are uniformly dispersed in 85 parts by weight of fluoride polymer, 4 parts by weight of antistatic agent are added, mixed evenly, and the mixture is uniformly deposited on the surface of the camera lens by vacuum sputtering or evaporation technology.
[0089] In this embodiment, the polyacrylate coating layer improves the dispersibility and stability of the nano-titanium dioxide particles and reduces surface defects; MXenes provide high conductivity and mechanical strength, and enhance the weather resistance and mechanical properties of the coating; the chemical bonds or strong interactions between the aluminum ions of the aluminum-based metal organic framework material and the nano-titanium dioxide particles enhance the stability of the composite material; the porous structure of the aluminum-based metal organic framework material can adsorb and store moisture and harmful gases, and improve the anti-corrosion performance; the fluoride polymer is used to provide excellent waterproof and dustproof properties and self-cleaning ability; the antistatic agent is used to prevent static electricity accumulation and improve image clarity.
[0090] Test example: The purpose of this test example is to compare the data of the four embodiments provided by the present invention with the prior art.
[0091] (1) Test materials:
[0092] Example 1: Iron-doped nano-titanium dioxide particles, 5 parts by weight; MXenes, 3 parts by weight; iron-based metal organic framework material (Fe-MIL-101), 2 parts by weight; silicone resin, 85 parts by weight; ultraviolet absorber, 5 parts by weight.
[0093] Example 2: Nitrogen-doped nano-titanium dioxide particles, 6 parts by weight; MXenes, 3 parts by weight; zinc-based metal organic framework material (ZIF-8), 3 parts by weight; polyurethane resin, 85 parts by weight; antioxidant additive, 3 parts by weight.
[0094] Example 3: Carbon nanotube-reinforced nano-titanium dioxide particles, 7 parts by weight; MXenes, 4 parts by weight; copper-based metal organic framework material (HKUST-1), 2 parts by weight; epoxy resin, 85 parts by weight; light stabilizer, 3 parts by weight.
[0095] Example 4: Nano-titanium dioxide particles coated with polyacrylate, 5 parts by weight; MXenes, 2 parts by weight; aluminum-based metal organic framework material (MIL-53 (Al)), 4 parts by weight; fluoride polymer, 85 parts by weight; antistatic agent, 4 parts by weight.
[0096] Comparative Example 1: 5 parts by weight of unmodified nano titanium dioxide particles; 85 parts by weight of silicone resin; and 5 parts by weight of ultraviolet absorber.
[0097] Comparative Example 2: unmodified nano titanium dioxide particles, 6 parts by weight; polyurethane resin, 85 parts by weight; antioxidant additive, 5 parts by weight;
[0098] Comparative Example 3: unmodified nano titanium dioxide particles, 7 parts by weight; epoxy resin, 85 parts by weight; light stabilizer, 5 parts by weight;
[0099] Comparative Example 4: 5 parts by weight of unmodified nano titanium dioxide particles; 85 parts by weight of fluoride polymer; and 4 parts by weight of antistatic agent.
[0100] (2) Test method:
[0101] According to the formulations provided in the above embodiments and comparative examples, corresponding layers were prepared;
[0102] The coating is applied evenly to the substrate (glass, metal and plastic) and cured under appropriate conditions.
[0103] (3) Performance test:
[0104] Weathering test: Use a UV weathering test chamber (QUV) to conduct 500 hours of accelerated weathering test to evaluate the color change, gloss and mechanical properties of the coating;
[0105] Wear resistance test: Use Taber wear tester to perform 1000 revolutions of wear test to measure the wear amount of the coating;
[0106] Corrosion resistance test: The coating samples were immersed in 3.5% NaCl solution for 7 days and the corrosion of the coating was observed;
[0107] Conductivity and thermal management testing: Use the four-probe method to measure the resistivity of the coating; use a thermal imager to measure the temperature distribution of the coating at high temperatures;
[0108] Optical performance test: Use a spectrophotometer to measure the transmittance and reflectance of the coating;
[0109] Antistatic performance test: Use a surface resistance tester to measure the surface resistance of the coating.
[0110] Table 1 Comparison of weather resistance test data
[0111]
[0112] Table 2 Comparison of wear resistance test data
[0113]
[0114]
[0115] Table 3 Corrosion resistance test data comparison
[0116]
[0117] Table 4 Comparison of conductivity and thermal management test data
[0118]
[0119]
[0120] Table 5 Comparison of optical performance test data
[0121]
[0122] Table 6 Antistatic performance test data comparison
[0123]
[0124] According to Tables 1 to 6, it can be seen that regarding weather resistance: the coating color of the embodiment changes less, while the coating color of the comparative example changes significantly; the glossiness of the coating of the embodiment decreases less, while the glossiness of the coating of the comparative example decreases significantly; the hardness and adhesion of the coating of the embodiment are maintained better, while the coating of the comparative example has obvious cracking and shedding. Regarding wear resistance: the coating of the embodiment has less wear, while the coating of the comparative example has greater wear; the coating surface of the embodiment is smooth without obvious scratches; the coating surface of the comparative example has obvious scratches and damage. Regarding corrosion resistance: the coating of the embodiment has no obvious corrosion, while the coating of the comparative example has obvious corrosion points and blistering. Regarding conductivity and thermal management: the coating of the embodiment has a lower resistivity, indicating that it has good conductivity; the coating of the comparative example has a higher resistivity; the coating of the embodiment has a uniform temperature distribution at high temperature and good heat dissipation effect; the coating of the comparative example has a higher local temperature and poor heat dissipation effect. Regarding optical properties: the coating of the embodiment has a higher light transmittance, while the coating of the comparative example has a lower light transmittance; the coating of the embodiment has a lower reflectivity, while the coating of the comparative example has a higher reflectivity. Regarding antistatic property: the coating surface resistance of the embodiment is lower, indicating that it has good antistatic property; the coating surface resistance of the comparative example is higher.
[0125] Through the above experiments and data comparison, it can be concluded that the wear-resistant and anti-corrosion coating provided by the present invention is superior to the prior art in terms of weather resistance, wear resistance, corrosion resistance, electrical conductivity and thermal management, optical properties and antistatic properties. The introduction of modified nano-titanium dioxide particles, MXenes and metal organic frameworks not only enhances the basic properties of the coating, but also gives the coating additional functions such as self-cleaning, antistatic, light stability, etc., further improving the overall performance of the coating.
[0126] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A wear-resistant and anti-corrosion coating, characterized in that: The invention comprises the following raw materials in parts by weight: Modified nano titanium dioxide particles, 5-7 parts by weight; MXenes, 2-4 parts by weight; Metal organic framework, 2-4 parts by weight; Resin material, 85 parts by weight; Additives, 3-5 parts by weight.
2. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The modified nano titanium dioxide particles are selected from the group consisting of iron-doped nano titanium dioxide particles, nitrogen-doped nano titanium dioxide particles, carbon nanotube-enhanced nano titanium dioxide particles, and nano titanium dioxide particles with polyacrylate coated on the surface.
3. The wear-resistant and anti-corrosion coating according to claim 2, characterized in that: The metal organic framework is one of an iron-based metal organic framework material, a zinc-based metal organic framework material, a copper-based metal organic framework material and an aluminum-based metal organic framework material.
4. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The resin material is one of silicone resin, polyurethane resin, epoxy resin or fluoride polymer.
5. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The additive is at least one of an ultraviolet absorber, an antioxidant additive, a light stabilizer, and an antistatic agent.
6. The wear-resistant and anti-corrosion coating according to claim 1, characterized in that: The MXenes are prepared by selectively etching the MAX phase.
7. The wear-resistant and anti-corrosion coating according to claim 3, characterized in that: The iron-based metal organic framework material, the zinc-based metal organic framework material, the copper-based metal organic framework material and the aluminum-based metal organic framework material are all prepared by a solvent thermal method.
8. A method for preparing the wear-resistant and anti-corrosion coating according to claim 6, characterized in that: The following steps are involved: S1. Modifying nano titanium dioxide by reinforcing materials to obtain modified nano titanium dioxide particles; S2, preparation of MXenes by selective etching of MAX phase; S3, preparation of metal organic frameworks by solvothermal method; S4. Mixing the modified nano-titanium dioxide particles, MXenes and metal organic frameworks with resin materials and additives to form a coating material.
9. The method for preparing the wear-resistant and anti-corrosion coating according to claim 8, characterized in that: The coating material prepared in S4 is used for optical electronic devices.
Citation Information
Patent Citations
Preparation method of composite metal organic framework material colloidal solution and application thereof in optical coatings
CN102061112A
Composite wave-absorbing material based on MXene and metal organic framework as well as preparation method and application of composite wave-absorbing material
CN112251193A
Preparation method and application of Fe-TiO2 / MIL-101 (Cr) composite photocatalytic material
CN118831650A
Anti-corrosion and wear-resistant coating with pH response and preparation method of anti-corrosion and wear-resistant coating
CN119081508A
Abrasion-resistant Anti-corrosive coating, and preparation method and use thereof
US20230078879A1
Cited By
Water pump shaft wear-resistant anticorrosive coating and preparation method thereof
CN122726728A